Soft Cardiac Patch Using a Bifacial Architecture of Adhesive/Low‐Impedance Hydrogel Nanocomposites and Highly Conductive Elastomer Nanocomposites - Jeeyoung Kim; Gi Doo Cha; Minsung Kim; Seung‐Pyo Lee; Sung‐Hyuk Sunwoo; Dae‐Hyeong Kim (Advanced NanoBiomed Research)
Soft implantable multichannel cardiac electrode arrays that establish direct monolithic interfaces with the heart are key components for advanced cardiac monitoring and electrical modulation. A significant technological advancement in this area is the development of stretchable conductive nanocomposites, fabricated through the integration of metallic nanomaterials and elastic polymers, aimed at achieving both high electrical conductivity and mechanical elasticity. Despite these advances, further progress in material performance and device designs is required to ensure seamless, reliable, biocompatible, and high‐fidelity cardiac interfacing. Herein, the development of a soft multichannel cardiac patch based on a bifacial architecture of adhesive/low‐impedance hydrogel nanocomposites and highly conductive elastomer nanocomposites is reported. The bifacial design facilitates the integration of the cardiac patch between the heart and other tissues/organs can be achieved. The hydrogel nanocomposite layer, positioned on the epicardial side, provides stable adhesion to the target cardiac tissue and enables low‐impedance biocompatible interfacing with the heart, while the elastomer nanocomposite layer, positioned on the opposite side, offers high electrical conductivity for facile electrophysiological signal transfer and a low‐friction surface minimizing unwanted interactions with surrounding tissues. The effectiveness of this bifacial patch in multiple applications involving various cardiac signal recordings and electromechanical modulation demonstrations is showcased.